Giorgio Agamben on Aesthetics and Criticism - Veronika Darida (ESPES, 2021)
Focusing on Giorgio Agamben’s early writings (The Man without Content, Stanzas, Infancy and History) this paper investigates the peculiar status of aesthetics that is disclosed by these texts, highlighting particularly the shift that emerges therein from aesthetic to ethical concerns. Agamben’s idea of a ‘destruction of aesthetics’ will bring attention to the question of the destination of aesthetics. The claim that only ruins can outline the original structure of works of art, providing a possible basis for creative criticism, will also be examined in the conclusion.